Pyridyl‐Functionalised 3H‐1, 2, 3, 4‐Triazaphospholes: Synthesis, Coordination Chemistry and Photophysical Properties of Low‐Coordinate Phosphorus Compounds. Issue 31 (26th June 2015) - Sklorz, Julian A. W.; Hoof, Santina; Rades, Nadine; De Rycke, Nicolas; Könczöl, László; Szieberth, Dénes; Weber, Manuela; Wiecko, Jelena; Nyulászi, László; Hissler, Muriel; Müller, Christian
Abstract Novel conjugated, pyridyl‐functionalised triazaphospholes with either tBu or SiMe3 substituents at the 5‐position of the N3PC heterocycle have been prepared by a [3+2] cycloaddition reaction and compared with structurally related, triazole‐based systems. Photoexcitation of the 2‐pyridyl‐substituted triazaphosphole gives rise to a significant fluorescence emission with a quantum yield of up to 12 %. In contrast, the all‐nitrogen triazole analogue shows no emission at all. DFT calculations indicate that the 2‐pyridyl substituted systems have a more rigid and planar structure than their 3‐ and 4‐pyridyl isomers. Time‐dependent (TD) DFT calculations show that only the 2‐pyridyl‐substituted triazaphosphole exhibits similar planar geometry, with matching conformational arrangements in the lowest energy excited state and the ground state; this helps to explain the enhanced emission intensity. The chelating P, N‐hybrid ligand forms a ReI complex of the type [(N^N)Re(CO)3Br] through the coordination of nitrogen atom N2 to the metal centre rather than through the phosphorus donor. Both structural and spectroscopic data indicate substantial π‐accepting character of the triazaphosphole, which is again in contrast to that of the all‐nitrogen‐containing triazoles. The synthesis and photophysical properties of a new class of phosphorus‐containing extended π systems are described.